Islam and Local Traditions in Kaur, Indonesia: Reorienting Ritual Meaning, Tawheed, and Socio-Religious Transformation - Juliansyah Juliansyah; Ani Jayanti (Yayasan Darusssalam Bengkulu, 2026)
This study examines the integration of Islam and local traditions in Kaur Regency, Bengkulu, Indonesia, with a focus on how Muslim communities reinterpret ancestral traditions within the framework of Islamic belief and socio-religious practice. Using a qualitative approach with an ethnographic-interpretive design, data were collected through in-depth interviews, participatory observation, and documentation of local traditions, including grave pilgrimage, nyeram, banquets or feasts, traditional medicine, dhikr-rudat art, and death rituals. The findings show that the integration of Islam and local traditions in Kaur occurs through three main processes. First, traditions previously associated with ancestral spirits, sacred objects, sacred places, and supernatural powers are reoriented toward the value of tawheed. Second, customary practices are adjusted to Islamic teachings through the inclusion of prayer, dhikr, tahlil, Qur’anic recitation, religious lectures, and the involvement of religious leaders. Third, local traditions function as spaces of social solidarity and religious education through mutual assistance, almsgiving, condolence rituals, oral traditions, and cultural da’wah. The study concludes that Islamization in Kaur does not simply eliminate local culture, but proceeds through selection, reinterpretation, and adaptation. These findings contribute to the study of local Islam by showing how Muslim communities negotiate belief, ritual, and religious change while maintaining local cultural identity.